2009
DOI: 10.1165/rcmb.2008-0302oc
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 Protects against Hyperoxia-Induced Mitochondrial Damage via Bcl-2–Induced Bak Interactions with Mitofusions

Abstract: Overexpression of IL-6 markedly diminishes hyperoxic lung injury, hyperoxia-induced cell death, and DNA fragmentation, and enhances Bcl-2 expression. We hypothesized that changes in the interactions between Bcl-2 family members play an important role in the IL-6-mediated protective response to oxidative stress. Consistent with this hypothesis, we found that IL-6 induced Bcl-2 expression, both in vivo and in vitro, disrupted interactions between proapoptotic and antiapoptotic factors, and suppressed H 2 O 2 -in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 34 publications
5
70
0
Order By: Relevance
“…The expression of NF-kB-regulated proand antiapoptotic proteins was assessed on the basis of previous reports linking them to hyperoxic exposure (10,32,33). Consistent with hyperoxia-induced NFkB activation, both WT and AKBI mice demonstrated induction of BAX mRNA and protein expression at 96 hours of exposure ( Figures 5A-5C).…”
Section: Antiapoptotic and Antioxidant Nf-kb Target Gene Expression Imentioning
confidence: 72%
See 1 more Smart Citation
“…The expression of NF-kB-regulated proand antiapoptotic proteins was assessed on the basis of previous reports linking them to hyperoxic exposure (10,32,33). Consistent with hyperoxia-induced NFkB activation, both WT and AKBI mice demonstrated induction of BAX mRNA and protein expression at 96 hours of exposure ( Figures 5A-5C).…”
Section: Antiapoptotic and Antioxidant Nf-kb Target Gene Expression Imentioning
confidence: 72%
“…Given these facts, both antiinflammatory and antiapoptotic strategies have been employed to attenuate hyperoxic lung injury. Although anti-inflammatory interventions have met variable success (5)(6)(7)(8)(9), increasing the expression of antiapoptotic factors in transgenic murine models results in attenuated hyperoxic lung injury (10)(11)(12). These studies suggest that preventing hyperoxia-induced apoptosis can prevent lung injury, but the transcriptional mechanism mediating expression of these factors is largely unknown.…”
mentioning
confidence: 99%
“…The present studies add to our understanding of the relationship(s) between BRP-39/YKL-40 and apoptosis by demonstrating that these chilectins inhibit the oxidant-induced cell death of alveolar type II cells. Although the mechanism of this protection is not clear, it is tempting to speculate that the phosphatidylinositol 3 kinase-Akt pathway is involved, because studies from our laboratory have demonstrated that BRP-39/YKL-40 is a potent activator of Akt (31), and Akt can confer cytoprotection in HALI (46)(47)(48)(49). In combination, these studies allow for the speculation that BRP-39 and YKL-40 are critical regulators of cell death that inhibit oxidant injury and confer structural cell cytoprotection at physiologic concentrations, and prolong the survival of inflammatory cells, and contribute to antigen sensitization, chronic inflammation, and tissue remodeling when elevated.…”
Section: Discussionmentioning
confidence: 99%
“…This has been related to the fundamental underlying function of Bcl-2 proteins, possibly in mitochondrial energetics (68), which influences mitochondrial morphology and function. Although the mechanism through which Bcl-2 family proteins regulate mitochondrial morphogenesis is not well understood, studies suggest close interactions between Bcl-2 family proteins and the dynamin-like GTPases Drp1 and MFN1/2 that physically mediate mitochondrial outer membrane fission and fusion, respectively (67,69,70). In this study we show that TREM-1 induces Bcl-2 and increases the expression of MFN1 and MFN2, which increases mitochondrial integrity and thus inhibits apoptosis.…”
Section: Discussionmentioning
confidence: 47%